Green Accounting, Corporate Governance and Firm Value in Southeast Asia Region - Darlis, Edfan; Kurnia, Pipin; Nurmayanti, Poppy; Agusti, Restu; Alamsyah, Mudrika; Supriono, Supriono; Silalahi, Sem Paulus (Journal of Accounting Research, Organization and Economics, 2024)
Objective This study is to investigate the relationship between green accounting, managerial ownership, institutional ownership, independent commissioners and audit committees on firm value of mining companies in Southeast Asia region including Indonesia, Malaysia, Thailand, the Philippines and Vietnam.Design/Methodology The method used is OLS with 500 samples of mining company observation data in the Southeast Asia for the 2016-2020 periods. GMM estimation is to address the potential endogeneity of the multiple variables used in the estimation, unobserved heterogeneity, and autocorrelation, which cannot be resolved with a fixed effect.Results This study found that institutional ownership has positive significant effect on the firm value. Independent commissioners and audit committees have negative significant relationship with firm value of mining companies in the Southeast Asia, while green accounting and managerial ownership have no effect on the firm value.Research Limitations/Implications There is no availability of data to access companys annual reports from several countries and the annual reports of several countries are not made in English, educational background and social relations are not considered in measuring the independent board of commissioners and the audit committee. The results of this study can be used by company management in providing information about the percentage required for institutional ownership as a consideration in making decisions to increase company value.Novelty/Originality The researcher's knowledge, this is the first research to investigate green accounting on firm value in mining company in the Southeast Asia region which is included in emerging markets.